Influence of Argon Addition on NO Conversion Efficiency and Optical Emission Spectroscopy in NO/N2/O2 Mixture by Non-thermal Plasma - of Automotive, School; Engineering, Traffic; University, Jiangsu; China *Corresponding author: Fax: +86 511 88797620 2009; Tel: +86 511 88797620 2622; E-mail: lixiaohua@ujs.edu.cn, P.R. (Asian Journal of Chemistry, 2013)
The experimental set-up of NO conversion in NO/N2/O2/Ar mixture by non-thermal plasma was established. The effects of applied voltage and Ar concentration on NO conversion efficiency, NO2 concentration and O3 concentration were studied. The chemical mechanism of NO conversion was also analyzed by combining with emission spectroscopy diagnosis. The results show that adding Ar in the NO/N2/O2 mixture can enhance the activation probability of the molecules at low Vp-p due to the penning effect. Furthermore, the electron density of NTP increases with Ar additive, which promotes the formation of N, O atoms. The conversion efficiency of NO rises with the increasing of Ar concentration. With high Vp-p, Ar additive has a negative effect on O3 generation and O3 concentration reduces with the increasing of Ar concentration. The variation of NO2 concentration is similar to that of O3 concentration.